STRENGTHENING CHARACTER EDUCATION IN ELEMENTARY SCHOOL WITH INTERNATIONAL CURRICULUM (A Case Study at Bestari Utami Elementary School, Garut) - Susanti, Santi; Sukaesih, Sukaesih (Sosiohumaniora, 2021)
Character education is necessary given to children from an early age, to manage their emotions and become individuals who have positive behavior for themselves and their surrounding environment in the future. The implication of good character education will make children do things consciously, committed, and competent, and grow into social beings who help each other, civilized and polite. This research aims to reveal the strengthening of character education for students at Bestari Utami elementary school in Garut. This school applies an entrepreneurial curriculum with international school learning methods, but still concerning character education to students based on the local cultural wisdom of Sundanese. This research uses a qualitative method with a case study approach. The primary data obtained through in-depth interviews with school managers and observations of learning activities at SD Bestari Utami. Secondary data obtained through literature and document reviews relevant to the research. Data analysis using interactive data analysis models from Miles and Huberman. The results showed that character education at SD Bestari Utami refers to equality and unity as a fundamental concept of school education. Children deserve to get quality education regardless of their ethnic, religion, and economic background. Strengthening character values based on Pancasila that comprises religious values, nationalism, independence, integrity, and cooperation are embodied through cultural arts lessons that are included in the school curriculum, as well as implementing learning that motivates children to be independent and able to work together with their friends. This study concludes that character education will be effective and give an impact if applied to students and school managers.